(untitled) (Global Journal of Human-Social Science, 2019)
Traditional Study Abroad SA programs offered by universities have a profound impact on the cultural awareness and adaptability of students who participate in these experiences However recently increased opportunities to engage in short-term SA experiences have prompted shifts in the planning and structuring of these trips to achieve the most impact on student development SA s are particularly valuable for Americans due to the relative lack of global traveling by American students compared to students from other countries Not coincidentally the likelihood of an American failing in a future expatriate assignment is also comparatively high versus additional nationalities although millennial Americans are more likely than any other group to receive such a position This makes prior intercultural experiences through activities such as SAs all the more important to this generation of Americans as a steppingstone to their careers This study will analyze the impact of two different styles and structures of trip tours and excursions on American SA students during a short-term experience